Separation Of Inheritance Assets And Its Implications In Indonesian Civil Law - Silaen, Riama Novalia (PT. Anagata Sembagi Education, 2024)
This research employs qualitative methods with a literature study approach to explore the legal phenomenon of inheritance separation in Indonesian civil law. This approach facilitates the collection, review, and analysis of relevant literary sources, including books, journal articles, regulations, and court decisions. The initial step involves identifying and collecting relevant literature, followed by an analysis to comprehend basic concepts, legal principles, and procedures. Researchers critically analyze the collected literature, identifying key issues, challenges, debates, and evaluating each source's relevance and validity. The research findings indicate that inherited assets are a significant part of Indonesian civil law, comprehensively regulated by the Civil Code. Articles in the Civil Code address the rights and obligations of heirs, inheritance separation procedures, and special conditions that must be met. The process aims to end joint ownership and distribute assets to each heir according to their rights. This must be done with all heirs' agreement or through a court decision in case of disputes. Article 1075 regulates dispute resolution, allowing courts to intervene and make final decisions. Provisions for the cancellation of inheritance separation protect heirs' rights, with Articles 1112 and 1116 providing a basis for cancellation if there is coercion, fraud, or actions harming more than a quarter of the inheritance value. Overall, Indonesian law offers comprehensive protection for all heirs, ensuring the inheritance process aligns with justice and applicable legal principles.